Analisis Pengaruh Nilai Tukar Dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia Tahun (2014-2023) - Syifa Aina Nurajizah; Sinta Allena; Ridho Utama; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of exchange rates and inflation on Indonesia's economic growth in the 2014-2023 period. Economic growth data is measured using the Economic Growth Percentage (GDP), while the exchange rate is measured by the Value of USD 1 in Rupiah, and inflation is measured by the Inflation Percentage (General). In this research, the author uses statistical analysis methods to examine the relationship between exchange rates, inflation and economic growth. The data used comes from trusted sources, such as the Central Statistics Agency (BPS) and Bank Indonesia (BI). The research results show that there is a relationship between the exchange rate and Indonesia's economic growth. A high exchange rate tends to have a negative impact on economic growth, because it can cause a decrease in net exports and a decrease in production levels. Apart from that, inflation also has an influence on economic growth. A high level of inflation can cause economic instability and have a negative impact on people's real income. Apart from that, this research also shows that both the exchange rate and inflation have a significant influence on Indonesia's economic growth. This second factor needs to be considered in efforts to advance the economy and achieve optimal economic stability. This research provides a better understanding of the factors that influence Indonesia's economic growth. It is hoped that the results of this research can be a reference for the government and economic actors in taking appropriate policies to accelerate economic growth and maintain economic stability.